For a material rationality of the rights of nature: a reflection from the Belo Monte plant and the papagaio Verdinho cases (Revista da Faculdade de Direito, Universidade de São Paulo, 2023)
This paper deals with the need to look at the field of the rights of nature from a methodological approach that favors a material view of its realization, in view of the concrete danger experienced by humanity and the threat to its own existence, not to mention the extinction of several species of fauna, flora and climate change, carrying out reflection based on selected doctrine and jurisprudence, extracting central points brought by them, proposing the adoption of a paradigm that privileges in the treatment of the rights of nature the search for the final increment of protection and preservation and, consequently, a practical result that can effectively impact for the benefit of life on the planet, taking this idea in a broad sense, not based on rationality, superiority and exclusivity of men’s interests, but on the notorious fact that we are beings inserted in a necessary and essential cosmopolitan interaction, since life and coexistence are undoubtedly one and embryonic, even relying on the visions and sensibilities of those so-called traditional peoples and the desired construction of a more harmonious way of the man/nature relationship, which certainly has repercussions on present and future generations.